2015
DOI: 10.1074/jbc.m115.666180
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin-3-rutinoside Inhibits Protein Disulfide Isomerase by Binding to Its b′x Domain

Abstract: Background: Quercetin-3-rutinoside is an inhibitor of protein disulfide isomerase, a potential target for antithrombotic therapy. Results: Quercetin-3-rutinoside induces a compact conformation in PDI and binds to PDI with an IC 50 of about 10 M. Conclusion: Quercetin-3-rutinoside interacts with the bЈx domain of protein disulfide isomerase with a 1:1 stoichiometry. Significance: The bЈx domain reverses the antithrombotic properties of quercetin-3-rutinoside in a thrombosis model in a live mouse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 26 publications
6
97
0
7
Order By: Relevance
“…Fig. 10 shows the effect of 1 and 10 μM rutin on the activity of PDI red , demonstrating attenuated reoxidation after 30 s. When challenged with 5 mM GSH, rutin succeeded in inhibiting PDI turnover activity, supporting a non-thiol based method of inhibition [26]. …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Fig. 10 shows the effect of 1 and 10 μM rutin on the activity of PDI red , demonstrating attenuated reoxidation after 30 s. When challenged with 5 mM GSH, rutin succeeded in inhibiting PDI turnover activity, supporting a non-thiol based method of inhibition [26]. …”
Section: Resultsmentioning
confidence: 98%
“…1D) as a reversible inhibitor of PDI [25]. Inhibition reflects binding of the flavonoid to the b'x domain of PDI rather than a covalent interaction with the CxxC motif of the a and a' domains of PDI red [26]. Since these studies used the less sensitive insulin reductase assay, we were interested in applying the BD-SS reoxidation and turnover assays to assess their suitability for high throughput applications.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The administration of quercetin-3-rutinoside similarly inhibited thrombus formation following vascular injury in mouse models of thrombosis (6). Quercetin-3-rutinoside blocks PDI activity by binding to the substrate-binding pocket on PDI and inducing a conformational change in the enzyme, which results in a more compact molecular envelope and reduces substrate binding (7). Structure-activity relationship assays showed that all quercetins tested that possessed a glycoside at the third position on the C ring inhibited PDI, including isoquercetin (6) (also known as quercetin-3-glucoside), which has improved bioavailability in humans compared with quercetin-3-rutinoside (8)(9)(10)(11).…”
Section: L I N I C a L M E D I C I N Ementioning
confidence: 99%